The Infant Cuddler Study: Evaluating the effectiveness of volunteer cuddling in infants with neonatal abstinence syndrome. Issue 7 (9th October 2019) - Hignell, Amanda; Carlyle, Karen; Bishop, Catherine; Murphy, Mary; Valenzano, Teresa; Turner, Suzanne; Sgro, Michael
Abstract: Objectives: St. Michael's Hospital launched a volunteer cuddling program for all infants admitted into the neonatal intensive care unit in October 2015. The program utilizes trained volunteers to cuddle infants when caregivers are not available. This was a pilot study to assess the impact of a volunteer cuddle program on length of stay (LOS) and feasibility of implementation of the program. Methods: A mixed methods approach was utilized to measure both quantitative and qualitative impact. A pilot cohort study with a retrospective control group assessed the feasibility of implementing a volunteer cuddling program for infants with neonatal abstinence syndrome (NAS). Length of stay was used as a surrogate marker to measure the impact of cuddling on infants being treated for Neonatal Abstinence Syndrome. Focus groups using semi-structured interviews were conducted with volunteers and nurses at the end of the pilot study. Results: LOS was reduced by 6.36 days (U=34, P=0.072) for infants with NAS in the volunteer cuddling program. Focus groups with both bedside nurses and program volunteers described a positive impact of cuddling programs on infants, families, staff, and volunteers alike. Conclusions: The study results suggest that the volunteer cuddling program may reduce LOS in infants with NAS and have potential economic savings on hospital resources. However, larger prospective cohort studies are needed to confirm these results.